2016
DOI: 10.2320/matertrans.m2015464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfur on the Sintering of Nickel Particles

Abstract: Sintering behavior of ne nickel powder with various surface sulfur content have been systematically investigated. The nickel powder with 150 ppm sulfur demonstrated the greatest density of the sinters, while the nickel powder with 300 ppm sulfur showed the lower density than the others. It was found that the appropriate content of surface sulfur enhanced the densi cation of ne nickel powder, which is mainly attributed the existence of solid solution sulfur in the nickel crystal structure. However, the excess s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…This is an interesting finding revealing that the observed sintering of U-samples is inhibited by the presence of H2S impurities. Indeed, T. Yoneima et al [56] reported that excess sulfur beyond the solubility limit in nickel contributed to the formation of nickel sulfide phases that prevent grain growth.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…This is an interesting finding revealing that the observed sintering of U-samples is inhibited by the presence of H2S impurities. Indeed, T. Yoneima et al [56] reported that excess sulfur beyond the solubility limit in nickel contributed to the formation of nickel sulfide phases that prevent grain growth.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…A small amount of sulphur can be added to the SOEC inlet gas which reduces the CH 4 formation activity to almost zero without sacrificing too much of the electrochemical activity [74]. Unfortunately, Sulphur also increases the sintering activity of Ni [75], which accelerates electrode degradation. This decreases the SOEC lifetime, thereby making Sulphur addition a less attractive approach.…”
Section: Renewable Methanolmentioning
confidence: 99%
“…It is necessary to manipulate selective impurities that can alter the adsorption properties such as the surface energy and surface anisotropy of Ni. We chose sulfur among the various elements that are adsorbed nonpreferentially on the Ni surface and cause a sintering delay effect that can eliminate the defects in MLCCs. , H 2 S is a suitable candidate for the easy adsorption of S to Ni. , However, H 2 S is toxic and dangerous for direct use in CVS. To overcome this problem, a suitable chemical that can locally produce H 2 S in a CVS reactor would be highly beneficial for controlling the shape of the Ni-NPs.…”
Section: Introductionmentioning
confidence: 99%
“…We chose sulfur among the various elements that are adsorbed nonpreferentially on the Ni surface and cause a sintering delay effect that can eliminate the defects in MLCCs. 23 , 24 H 2 S is a suitable candidate for the easy adsorption of S to Ni. 25 , 26 However, H 2 S is toxic and dangerous for direct use in CVS.…”
Section: Introductionmentioning
confidence: 99%